Workshop Penelitian Tindakan Kelas (PTK) dan Publikasi Artikel Ilmiah ke Jurnal Nasional bagi Guru di MAN Demak - Zuhri, Muhammad Saifuddin; Nursyahidah, Farida; Rubowo, Maya Rini; Roshayanti, Fenny; Sugiyanti, Sugiyanti (Perkumpulan Kualitama Edukatika Indonesia, 2024)
This activity aims to accompany teachers at MA Negeri Demak in Classroom Action Research (PTK) as well as the publication of scientific articles in national journals. The output of this activity is that teachers at MA Negeri Demak take PTK training so that they can make proposals, carry out PTK in class, prepare PTK reports and write scientific articles to be published in national journals. The workshop was carried out in groups using an andragogic approach. The training method is carried out using questions and answers, lectures, discussions, demonstrations, exercises and practice. The material is presented 25% theoretically and 75% practically. The research location is in the Demak State MA hall/meeting room. The material provided to teachers to improve cognitive abilities and PTK practice includes basic PTK concepts, PTK procedures, techniques for preparing PTK proposals, techniques for making PTK data collection instruments, techniques for preparing PTK reports, and techniques for preparing articles for National journals.